2019
DOI: 10.3390/met9090969
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Failure of AISI 304 Stainless Steel Tubes in a Gas Heater Unit

Abstract: This paper investigates a failure in convection section tubes of a gas heater unit in a petrochemical plant. Tubes are made of AISI 304 stainless steel. The failure is reported after 5 years of service at working temperature 500 °C. The failure is in the form of circumferential cracks in the vicinity of the weld. Various characterization techniques, including optical and electron microscopes as well as energy-dispersive X-ray spectroscopy (EDS), were used to study the failure. Results showed that that the dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This certainly has positive implications for the system reliability and service life of a gas turbine. Lessons learnt from a failure study will certainly be useful in planning failure mitigation strategies in similar plants/set-ups [21][22][23][24][25][26][27][28][29][30]. It will be shown that the failure, reported in this study, is a corrosion-fatigue failure.…”
Section: Introductionmentioning
confidence: 68%
“…This certainly has positive implications for the system reliability and service life of a gas turbine. Lessons learnt from a failure study will certainly be useful in planning failure mitigation strategies in similar plants/set-ups [21][22][23][24][25][26][27][28][29][30]. It will be shown that the failure, reported in this study, is a corrosion-fatigue failure.…”
Section: Introductionmentioning
confidence: 68%
“…On the other hand, Figure 10 exhibits the variation of hardness in the three model RHEA coatings milled for 24 h. The WMoNbTaV HEA coating has the highest average hardness value of 1205 HV 0.025; however, the coating after annealing shows a relatively low hardness value (967 HV 0.025 on average). It should be pointed out that 304 stainless-steel substrates are intrinsically subject to embrittlement due to precipitation of second phases when exposed to high temperature for a long time [37]. However, annealing of the substrate is not a primary goal and beyond the scope of this study.…”
Section: Sem Observation/eds Analysismentioning
confidence: 99%
“…(i) Casting and Metal Forming [6,7,11,13,15,19,[24][25][26] (ii) Machining [12,16,20] (iii) Chemical/Petrochemical [3,17,21,23] (iv) Heat Treatment [22] (v) General Plant Machinery [1,9,18,24] b. Fatigue and Cyclic Loading [8,9,18]; c. Corrosion and Environmentally Assisted Cracking [3,5,11,21]; d. Wear and Surface Degradation [1,24,27].…”
Section: Contributionsmentioning
confidence: 99%
“…(i) Casting and Metal Forming [6,7,11,13,15,19,[24][25][26] (ii) Machining [12,16,20] (iii) Chemical/Petrochemical [3,17,21,23] (iv) Heat Treatment [22] (v) General Plant Machinery [1,9,18,24] The metal component manufacturing industry (casting, metal forming, and machining) seems to be highly involved, as one of the primary industrial component production sectors, in highlighting the efforts in understanding material behavior and taking actions for failure prediction and prevention.…”
Section: Contributionsmentioning
confidence: 99%